تدبّر وبيان في الدّقة والإحكام في القرآن: آيتا الشمس والقمر نموذجًا (Journal of Academic Research, 2025)
AbstractBy the wisdom of Allah Almighty, the final revelation was ordained in clear Arabic—a language that preserves its foundational roots while brilliantly harmonizing with new developments. Rarely does the meaning of an ancient word elude the contemplator today, but what often proves challenging is reconciling the imagery of the past with modern scientific revelations. The mental image people once had of the sun and the moon, for instance, is no longer acceptable to the rational mind today. No sensible person today would accept the notion of the sun "disappearing" on Earth, for everyone understands that sunset in one region means sunrise in another... All this calls for profound reflection upon the infallible (Quran), and for such reflection to be conducted with a fair-minded intellect—one that recognizes the Quran needs nothing but a sincere, unbiased, and honest gaze to reveal its precision, perfection, and wonders.This research highlights the miraculous nature of Quranic discourse, which remains flawless despite the varying circumstances and eras of its recipients. The imagery employed in it is meticulously crafted, with its brilliance becoming ever more apparent as scientific truths unfold.